International Relations Theory and the Asia-Pacific - G. John Ikenberry, Michael Mastanduno (Columbia University Press, 2003)
Since the end of the cold war, the problems and prospects of the Asia-Pacific region have drawn increased attention from students of international politics and foreign policy. Interactions among the major powers of the region—the United States, China, and Japan—have taken on a particular significance. Scholars seeking to explore these renewed relationships in a dynamic and uncertain international context face a double challenge. One challenge is to bridge the gap between the rich comparative and foreign policy scholarship on China, Japan, and the United States, on the one hand, and the wider world of international relations theory on the other. The two worlds of area specialty and international relations theory often do not meet. As a result, policy debates about the stability of Asia-Pacific relations tend to be under-theorized, while theoretical arguments about the region are often undertaken without the benefit of historical or comparative perspective. The contributors to this volume begin with the premise that the theoretical insights of international relations need to be brought more closely into contact with the rich history and complex reality of the Asia-Pacific region. Since there should be a payoff for both worlds, the chapters below are motivated collectively by this goal of helping to bridge the gap and bring theory to bear on the international politics and economics of the region. In doing so, a second interesting challenge emerges. International relations scholars, particularly those trained in the United States, employ theories that emerged in the context of the Western historical experience. American international relations theories are deeply rooted in Western philosophical traditions and debates, with an intellectual lineage traced back to Hobbes, Rousseau, Kant, Locke, Marx, and others classic thinkers. It is not immediately apparent— nor should it be taken for granted—that these theories or intellectual constructs are relevant to understanding Chinese, Japanese, or Korean calculations and behavior. This volume necessarily raises the question of the usefulness and fit of European-centered theories for the Asia-Pacific region. In this sense as well, we believe that the encounter between the Asia-Pacific region and international relations scholarship can only illuminate and enrich both realms.